2015
DOI: 10.1007/s10384-015-0380-6
|View full text |Cite
|
Sign up to set email alerts
|

Increased choroidal blood flow velocity with regression of unilateral acute idiopathic maculopathy

Abstract: These results reveal that there is a significant elevation of choroidal blood flow velocity and substantial reduction of choroidal thickness with regression of UAIM, suggesting that impaired choroidal circulation may be involved in the pathogenesis of UAIM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 23 publications
3
32
0
Order By: Relevance
“…And even despite the fact that LSFG has on occasion been used to analyze the blood flow of the optic disc in glaucomatous eyes, there have been few reports that have used LSFG as a clinical diagnostic tool. [12, 26] A previous report showed that LSFG could be used to monitor changes in the ocular blood flow caused by nonischemic type central retinal vein occlusion. [27] Our results also suggested that LSFG-wide could be used for non-invasive observation of the circulatory dynamics in the posterior region, including the optic disc and macular lesions.…”
Section: Discussionmentioning
confidence: 99%
“…And even despite the fact that LSFG has on occasion been used to analyze the blood flow of the optic disc in glaucomatous eyes, there have been few reports that have used LSFG as a clinical diagnostic tool. [12, 26] A previous report showed that LSFG could be used to monitor changes in the ocular blood flow caused by nonischemic type central retinal vein occlusion. [27] Our results also suggested that LSFG-wide could be used for non-invasive observation of the circulatory dynamics in the posterior region, including the optic disc and macular lesions.…”
Section: Discussionmentioning
confidence: 99%
“…S1A; right, dotted line). To evaluate changes in average MBR, the changing rate of average MBR against the initial baseline value was used, as previously described, 17,[19][20][21][22][23][24][25][26] since the MBR is an index of ''relative'' blood flow velocity. …”
Section: Mean Blur Rate Measurements On Lsfgmentioning
confidence: 99%
“…The macular MBR, largely derived from the choroid, 16 has been used to evaluate choroidal hemodynamics in various diseases. [17][18][19][20][21][22][23][24][25][26] Our recent study on CSC demonstrates that the macular MBR increases at the acute stage, 19 reinforcing the suspected role of choroidal hyperperfusion in the development of acute CSC. 10 With recent advances of LSFG, various parameters can be automatically calculated to analyze the pulse waveform of MBR averaged in a single heartbeat, 14,[27][28][29][30][31] including the skew, blowout time (BOT), and acceleration time index (ATI), all of which are expressed as absolute values.…”
mentioning
confidence: 99%
“…Changes in the blood flow and thickness may be manifestations of a process with an “inflammatory” pattern occurring in the choroid [18, 25]. Similarly, these changes have been also observed in unilateral acute idiopathic maculopathy [20], acute posterior multifocal placoid pigment epitheliopathy [26], and acute zonal occult outer retinopathy complex [17, 19, 27–30]. In contrast, both the blood flow velocity and thickness increased in the acute stage of central serous chorioretinopathy [16, 31], which involves a sympathetic or adrenergic etiology.…”
Section: Discussionmentioning
confidence: 99%
“…The software automatically set each circle at the same site where a previous circle had been set at baseline during follow-up. To evaluate changes in average MBR, which is a quantitative index of the “relative” blood flow velocity, the changing rates of average MBR against the initial baseline values (defined as 100%) were utilized, as previously described [1620]. …”
Section: Case Presentationmentioning
confidence: 99%